Pengentasan Kemiskinan melalui Keuangan Sosial Islam: Integrasi Literasi Keuangan Syariah, Zakat, dan Wakaf dalam Perspektif Maqashid al-Syari'ah - Dicky Faldy Prayoga; Wahyu Wibowo; Taufikur Rohman; Aminuddin Aminuddin; Mohammad Rifan Firmansyah (Tadabbur: Jurnal Integrasi Keilmuan, 2026)
In developing countries, including Indonesia, poverty is still a major problem that impacts economic growth and public welfare. Although various government programs have been implemented, their effectiveness still requires performance improvement. The purpose of this study is to see how Islamic financial literacy, as well as how effective the management of zakat and waqf, contribute to poverty reduction in Indonesia. This study investigates the concept of poverty, ways to manage zakat and waqf, and their impact on public welfare. This study uses a qualitative method based on literature studies. The results of the study indicate that zakat has a strategic role in distributing wealth directly to the poor. On the other hand, productive waqf can create a sustainable source of funding for economic empowerment. The main challenges in optimizing this instrument are the lack of knowledge about Islamic finance and the lack of clarity in the management of zakat and waqf. Therefore, increasing public financial knowledge, collaboration between zakat and waqf institutions, and strengthening a more professional and accountable management system are needed. Zakat and waqf can help overcome poverty sustainably in Indonesia if implemented properly.